Time trends in mechanical thrombectomy (2017–2021): do real-world data reflect advances in evidence? - Christoph Riegler; Christoph Riegler; Viktoria Rücker; Regina von Rennenberg; Regina von Rennenberg; Kerstin Bollweg; Kerstin Bollweg; Bastian Cheng; Anna C. Alegiani; Fabian Flottmann; Marlena Schnieder; Marielle Ernst; et al. (Frontiers in Neurology)
BackgroundIn recent years, we have witnessed a continuous, evidence-based expansion of indications for endovascular therapy (EVT) in the treatment of ischaemic stroke, driven by advancements in extended time windows and target vessel occlusion. Our study aimed to evaluate the temporal changes in patients’ characteristics, treatment, and outcomes in clinical practice.MethodsWe used data from the German Stroke Registry, a large national multicentre prospective registry, which includes all patients receiving EVT for ischaemic stroke at its participating centers. We analysed baseline factors, treatment details, and clinical outcomes [Modified Rankin Scale (mRS) at 3 months] over a 5-year period (2017–2021).ResultsWe included 6,251 patients from eight centres. Over time, the characteristics of patients undergoing EVT changed in several aspects (2017 vs. 2021). Patients became older (median age from 76 [IQR: 65–82] to 77 [65–84 years]; ptrend = 0.02), and less severely affected (NIHSS from 15 [11–19] to 13 [8–18]; ptrend <0.001). There was an increase in patients treated more than 6 h after last seen well (22.0% to 28.3%; ptrend<0.001), and more patients were treated for medium vessel occlusion (16.1% to 28.1%; ptrend<0.001). The use of intravenous thrombolysis decreased (52.4% to 40.4%; ptrend<0.01). Good functional outcome declined (percentage of patients with mRS ≤ 2 from 36.0 to 34.9%; aOR 0.94 per year [0.89–0.99]), while mortality at 3 months increased from 25.3% in 2017 to 34.7% in 2021; aOR 1.13 per year [1.07–1.19].ConclusionBetween 2017 and 2021, there were significant shifts in the demographic and clinical profiles of patients undergoing EVT, along with an expansion in EVT indications. Despite these patients presenting with less severe stroke symptoms, improvements in functional outcomes were not observed, and mortality rates increased. These trends may reflect willingness to treat patients with more severe underlying health conditions.